The impact of pork‐barrel capital funding in schools: Evidence from participatory budgeting in NYC. (16th December 2021) - Rothbart, Michah W.; Schwegman, David J.; Shybalkina, Iuliia
Abstract: Pork‐barrel spending is a form of public spending controlled by individual legislators and primarily serving a local interest. In this paper, we investigate the impact of a type of pork, council member capital discretionary education spending voted upon in a participatory budgeting (PB) process, on school budgets and performance in New York City. Exploiting plausibly exogenous variation in discretionary spending induced by the PB elections, we find winning a PB election increases school pork appropriations. However, we find no evidence these transfers from council members improve fiscal and performance outcomes. Further, pork may interfere with school budgeting. Applications for practice: Even though NYC participatory budgeting elections are nonbinding, NYC council members fund capital projects that win these elections. As a result, winning schools experience large appropriation increases. We call this discretionary funding designated by one council member "pork" funding. Pork funding did not significantly affect fiscal outcomes (operating spending) or academic performance (test scores and attendance). We can rule out large changes for both, although medium‐sized improvements in school environment perception are possible. Estimates suggest participatory budgeting projects—and the pork they precipitate—may have small disruptive effects on school budgets by shifting resources from instruction and student support to building services. Qualitative data also suggest participatory budgeting projects may lack coordination with school budgets. Pork funding may increase total capital resources in recipient schools. However, the timing of capital expenditures limits power to identify the size of this effect or rule out the crowd‐out of other capital resources.